First man the life of Neil A. Armstrong - Hansen, James R. (Simon & Schuster, 2018)
On July 20, 1969, the world stood still to watch 38-year-old American astronaut Neil A. Armstrong become the first person to step on the surface of another heavenly body. Perhaps no words in human history became better known than those few he uttered at that historic moment. This essential biography, now updated with a new chapter written after Armstrong's death, addresses the complex legacy of the First Man, as both an astronaut and an individual.--From publisher description.